2004
DOI: 10.1080/00016470410001394
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of primary total hip replacements in standard and ultra-clean operating theaters detected by the polymerase chain reaction

Abstract: Wound contamination of primary THR occurs frequently in both standard and ultra-clean operating theaters and contamination is greater at the end of surgery than at the beginning (p=0.04). In this small series, we found no differences in wound contamination between standard and ultra-clean theaters (p=0.1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…To be most effective, key operating theatre staff should wear body exhaust suits while working in the ultraclean environment 1 34. However, standard culture techniques by air sampling or landing ‘mode’ as a method to assess potential wound contamination do not directly correlate with wound contamination, and they are at best surrogate measures representing the degree of air contamination at the point of sampling, which might be some distance away from the implant zone 35. There was also evidence that wound contamination was greater at the end of surgery than at the beginning 35…”
Section: Discussionmentioning
confidence: 99%
“…To be most effective, key operating theatre staff should wear body exhaust suits while working in the ultraclean environment 1 34. However, standard culture techniques by air sampling or landing ‘mode’ as a method to assess potential wound contamination do not directly correlate with wound contamination, and they are at best surrogate measures representing the degree of air contamination at the point of sampling, which might be some distance away from the implant zone 35. There was also evidence that wound contamination was greater at the end of surgery than at the beginning 35…”
Section: Discussionmentioning
confidence: 99%
“…Others have found that bacterial contamination of the wound in THR was not reduced with laminar-flow ventilation. 18 In order to be effective, laminar flow requires no obstructions to the path of the high flow of air. Obstructions cause eddies which in turn can produce areas of risk for increasing contamination and infection.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation could be that the cementation per se in some way creates conditions that are conducive to the growth of bacteria following the apparently unavoidable contamination peroperatively (Davis et al 1999, Clarke et al 2004a, Maathuis et al 2005. Necrotic bone tissue around the cement, caused by cement toxicity or heat generation during curing of the cement, could be the potential growth medium.…”
Section: Discussionmentioning
confidence: 99%
“…Peroperative wound contamination during implantation of primary total hip arthroplasties (THAs) occurs in more than 30% of all operations in standard and in ultra-clean operating theaters (Davis et al 1999, Clarke et al 2004a, b, Maathuis et al 2005. Many THAs are considered to fail due to the presence of clinically unrecognized low-grade infection.…”
mentioning
confidence: 99%